Evaluation of depth-wise post-gel polymerisation shrinkage behaviour of flowable dental composites. (December 2021) - Behl, Sonam; Rajan, Ginu; Raju,; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Short fibre reinforced flowable dental composites are gaining acceptance over particulate filled composites due to their competence to impart improved physio-mechanical properties and capability to prevent crack propagation. However, limited research exists to assess their overall post-gel shrinkage behaviour, which is an important factor to determine marginal seal around restoration and hence its longevity. In this paper, depth-wise post-gel shrinkage strain and the resulting factors such as degree of conversion and rheological behaviour of flowable fibre reinforced composite (FRC) containing 5% weight fraction of 5 μm diameter, 350 μm length S-Glass fibres in UDMA/TEGDMA mixture along with 50% strontium filler particles were investigated. Post-gel shrinkage strain was measured using an array of optical fibre Bragg grating sensors (FBGs) of diameter 250 μm and length 1 mm each embedded at three different depths (depth 0 mm, depth 2.5 mm and depth 5 mm from curing light tip) within the flowable dental composite samples. The rheological behaviour during the polymerisation process was carried out using dynamic oscillatory tests. To evaluate the conversion of CC during polymerisation, degree of conversion tests were conducted by using FTIR spectroscopy. The results obtained for FRC samples were further compared with that of particulate filled composite (PFC) samples, with 55% strontium filler particles only within the same resin system. The relationship between post-gel shrinkage strain at different depths, rheological behaviour and degree of conversion was also explored. The experimental results from the sensor embedded materials suggested that the post-gel shrinkage strain was higher at the top surface (depth 0 mm) and was 50% more than at the bottom surface (depth of 5 mm) for dental FRC as well as PFC samples. Further, similar flow behaviour and not significant different (p<0.05) degree of conversion (DC), post-gel shrinkage strain for dental PFC and FRC composites was observed, establishing a convincing positive relationship between all the key factors and further implying that replacement of fibres with fillers did not affect the overall post-gel polymerisation shrinkage behaviour in dental composites. This investigation has also demonstrated that fibre optic sensors-based shrinkage measurements can be an ideal technique to evaluate post-gel shrinkage performance of dental resins with PFCs or FRCs.